Challenges in Research on Preferences and Personality Traits: Measurement, Stability, and Inference - Bart H.H. Golsteyn; Hannah Schildberg-Hörisch (Institute of Labor Economics (IZA), 2017)
This paper reviews several traditions in economic research on preferences as well as research on personality traits in personality psychology and lists challenges in both fields. We discuss challenges regarding the measurement of preferences and personality traits, challenges regarding the stability of preferences and traits, and challenges when inferring causality. Additionally, we highlight areas in which we see potential benefits from taking into account methodological approaches or insights from the respective other discipline.
Keywords: A12; D03; 330; preferences; personality traits; measurement; stability; causality